Bridging our mandates: evidence-based practice (EBP) and patient-centered care (PCC) 1 - Ratner, Nan Bernstein (Henry Stewart Talks, 2017)
Principles of evidence-based practice (EBP), The process model, Linear vs. continuous EBP, Changing therapy approaches, Treatment of early stuttering, The acceptable time to wait for therapy progress, Patient-centered care (PCC), Seeking a single best therapy for any condition, Important questions that need asking